Product Development of Sweetened Condensed Rice Milk from Rai Dok Kha Phang Nga Rice - Khongkaew, Janya; Grutpisamai, Pitsamai; Suteebut, Nomjit (RMUTP Research Journal Sciences and Technology, 2024)
The objectives of this research were to formulate sweetened condensed rice milk from Rai Dok Kha Phang Nga rice by studying the ratio of rice to water in a rice milk preparation step, to study the suitable amount of Luo Han Kuo powder used as a sweetener for sucrose substitute, to study the appropriate amount of supplementation with rice protein powder, and to analyze nutritional values of sweetened condensed rice milk product. The sweetened condensed rice milk obtained at each stage was evaluated for quality and statistical analysis. From the experiment, it was found that a ratio of crushed rice mixed with water affects the concentration of the product. From the results of sensory evaluation, it was found that the preparation of rice milk using Dok Kha rice mixed with water at a ratio of 10:40 received a higher preference score than using the ratios of 5:45 and 15:35 (p≤0.05). The use of Luo Han Kuo sugar powder sweetened replaced 30% sugar resulted in the product having a higher preference score than substitutions of 40% and 50% (p≤0.05). By adding rice protein powder, the sweetened condensed rice milk products had a lighter color. The viscosity was higher, and panelists rated the sweetened condensed rice milk product fortified with 4% rice protein powder more highly than those fortified with 2% and 6%.(p≤0.05). The developed sweetened condensed rice milk product consists of 46% Phang Nga rice milk, 35% granulated sugar, 15% Luo Hang Kuay sugar powder, and 4% rice protein powder. The 100 g of developed sweetened condensed rice milk was 215.66 kcal with a protein content of 3.03 g, 0.82 g of fat, 49.04 g of carbohydrates, and 8.88 mg of anthocyanins.